2006
DOI: 10.1111/j.1749-4486.2006.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast in allergic rhinitis: a systematic review and meta‐analysis

Abstract: Allergic rhinitis is common. This systematic review outlines the evidence regarding montelukast in allergic rhinitis and provides a meta-analysis of its efficacy. The evidence suggests that montelukast does reduce nasal symptom score by 3.4% (95% CI: 2.5% to 4.2%) when compared with placebo. Montelukast is not as effective as topical nasal steroids or antihistamines and should therefore be regarded as second line therapy. When used, montelukast should be used in combination with an antihistamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…Montelukast, which significantly reduced daytime nasal, eye and throat symptoms, nighttime symptoms, and symptoms affecting quality of life (QL) in adult patients with seasonal AR (Grainger and Drake-Lee, 2006;Nayak and Langdon, 2007;Bousquet et al, 2009), has also been demonstrated to be safe in children (Bisgaard et al, 2009). Similar results have also been obtained with zafirlukast (Piatti et al, 2003) and pranlukast (Ueda et al, 2003;Okubo and Baba, 2008).…”
Section: New Potential Therapeutic Applications Of Leukotriene Recsupporting
confidence: 69%
“…Montelukast, which significantly reduced daytime nasal, eye and throat symptoms, nighttime symptoms, and symptoms affecting quality of life (QL) in adult patients with seasonal AR (Grainger and Drake-Lee, 2006;Nayak and Langdon, 2007;Bousquet et al, 2009), has also been demonstrated to be safe in children (Bisgaard et al, 2009). Similar results have also been obtained with zafirlukast (Piatti et al, 2003) and pranlukast (Ueda et al, 2003;Okubo and Baba, 2008).…”
Section: New Potential Therapeutic Applications Of Leukotriene Recsupporting
confidence: 69%
“…86 Pediatric and adult-based literature does indicate that montelukast may have a significant benefit in improving nasal symptoms and lung function in those with comorbid allergic rhinitis and asthma. 87,88 Biologic therapies are increasingly being recognized as a potential treatment for moderate to severe persistent asthmatics who do not respond to conventional asthma therapies. Omalizumab is a monoclonal antibody that selectively binds to IgE and is indicated in patients as young as 6 years of age in Europe and >12 years of age in the…”
Section: Assessment and Monitoringmentioning
confidence: 99%
“…They are effective in controlling sneezing, nasal pruritus, rhinorrhea, and nasal congestion associated with allergic rhinitis [6,[62][63][64][65][66]. Leukotriene-receptor antagonists are less effective than intranasal corticosteroids but equivalent to oral antihistamines in the treatment of seasonal allergic rhinitis [67,68].…”
Section: Leukotrienes Receptor Antagonistsmentioning
confidence: 99%